An exploratory study on the sociocultural consequences of food consumption patterns among African American girls. (1st November 2021) - Stovall, Tony; Mitchell, Natalie A.; Smith, Farouk; Jones, Ross
Abstract: African American women, in particular, have learned to navigate through a food consumption landscape that purposefully, and often aggressively, limits their choices and stigmatizes their resulting physical appearance, and renders them collectively unattractive and unworthy. While American women are challenged to subscribe to traditional slim body standards, a faction of Americans have differing opinions. African American (AA) women celebrate larger body types and defy weight stigma. When African Americans make food choices, taste and cost are not the only factors influencing those choices; the cultural role of food is also considered. We conducted semi-structured interviews with 12 African American girls to identify some of the consequences of this consumption practice that challenges what we argue is a hegemonic taste regime surrounding body size. This work further elucidates the ways in which the African American community has operationalized the concept of cultural capital around the issues of body image to create what we suggest is a type of emotional well-being. In addition to uncovering marketing channels promoting anti-obesity campaigns that would be more likely to capture their attention, our findings also reveal that AA girls embrace shapely bodies, despite not necessarily having one themselves, and overall possess a more positive body image than their Caucasian peers. Having shapely bodies was deemed more attractive among romantic interests and acceptable overall in the AA community regardless of the associated health risks associated with consuming unhealthy foods.